Determining the Spectrum of Pathologies on FNAC Evaluation of Peripheral Lymph Nodes at a Tertiary Care Center in Hyderabad, India - Ramanan Duraiswami; Sujatha Margam; Priya Chandran; Akina Prakash (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
Fine Needle Aspiration Cytology (FNAC) is an important diagnostic procedure used for rapid evaluation of a multitude of lesions. One of the common uses is for diagnosis of the underlying pathology of enlarged lymph nodes. The study’s goal was to look at the pattern of diseases seen on Fine needle aspiration (FNA) of enlarged superficial lymph nodes in a tertiary hospital in Hyderabad from January 2014 to August 2016, as well as to determine the patient profile who underwent this surgery at our hospital. To ascertain the age and sex distribution of the patients as well as the distribution of pathologies identified on FNA evaluation of the lymph nodes, data pertaining to the patients who underwent FNA evaluation of superficial lymph nodes from January 2014 to 31 August 2016 at a tertiary hospital located in Hyderabad, Telangana, were analyzed. The majority of the patients who underwent FNA evaluation of lymph nodes were females (61%; 156 out of 253 patients). The bulk of the patients were between the ages of 20 and 50. The most common diagnosis in our dataset (49.8%; 126 instances out of 253 FNA examinations) was reactive lymph node hyperplasia. The second most common diagnosis (37.15%; 94 out of 253 FNA assessments) was granulomatous lymphadenitis. The disease causing enlarged superficial lymph nodes can be accurately diagnosed by fine needle aspiration examination, which is quick, simple, relatively non-traumatic, and reliable in the hands of experts. The two most frequent causes of enlarged lymph nodes in our series were granulomatous lymphadenitis and reactive lymph node hyperplasia.